Out-of-Hospital screening for HIV, HBV, HCV and Syphilis in a vulnerable population, a public health challenge. Issue 6 (3rd June 2017) - Legoupil, C.; Peltier, A.; Henry Kagan, V.; Segouin, C.; Alberti, C.; de Massé, Luc; Shelly, M.; Krastinova, E.
ABSTRACT: We explored rates of Hepatitis B virus (HBV), Human Immunodeficiency Virus, Hepatitis C virus and Syphilis in a vulnerable population (mostly intravenous drug users, sex workers and homeless people) and focused on factors associated with failure to return for results (FTR) and with having a false perception (FP) of Immunization against HBV. We performed a prospective multicenter observational study in nine mobile (Out-of-Hospital) areas of screening located in Paris from 1 January 2014 through 31 December 2014. A total of 341 patients were recruited. The proportion of FTR for results was 38.75%. In multivariate analysis, unemployment was significantly associated with FTR (OR = 4.29; IC = [1.12; 16.39]), as well as having been screened in the past (OR = 4.32, IC = [1.70; 10.97]); 18.03% of patients had a FP of an Immunization against HBV. In multivariate analysis, having one's own place of residence protected against FP (OR = 0.33, [0.12; 0.95]), while being screened in the past enhanced the risk of FP (OR = 3.28, IC = [1.06; 10.11]). The rate of FTR is a problem and use of currently available technologies, such as phone texting, might be a partial solution in conjunction with rapid tests for diagnosis. In addition, more information and comprehension of the results should be provided together with specific anti-HBV vaccination campaigns targeting these specific populations.